2022
DOI: 10.1186/s13071-022-05381-w
|View full text |Cite
|
Sign up to set email alerts
|

Microbial ecology of sand fly breeding sites: aging and larval conditioning alter the bacterial community composition of rearing substrates

Abstract: Background Sand flies vector several human pathogens, including Leishmania species, which cause leishmaniases. A leishmaniasis vaccine does not yet exist, so the most common prevention strategies involve personal protection and insecticide spraying. However, insecticides can impact non-target organisms and are becoming less effective because of the evolution of resistance. An alternative control strategy is the attract-and-kill approach, where the vector is lured to a lethal trap, ideally locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The limited impact of vegetation cover on the incidence of CL can be observed from the GAM outputs, where the effect is only prominent within the range of 0.01 to 0.2, potentially indicating the true dynamic of the disease as some other studies proved that the limited vegetation cover creates favorable conditions for sand flies by increasing temperature and evaporation. 53 In fact a study on the presence of P papatasi, the major vector of CL, was conducted using a genetic algorithm for rule-set production and maximum entropy techniques. Both models revealed that the central and northern regions of the province, with lowland areas, were more susceptible to P papatasi propagation compared to the southern parts, characterized by mountainous and forested areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited impact of vegetation cover on the incidence of CL can be observed from the GAM outputs, where the effect is only prominent within the range of 0.01 to 0.2, potentially indicating the true dynamic of the disease as some other studies proved that the limited vegetation cover creates favorable conditions for sand flies by increasing temperature and evaporation. 53 In fact a study on the presence of P papatasi, the major vector of CL, was conducted using a genetic algorithm for rule-set production and maximum entropy techniques. Both models revealed that the central and northern regions of the province, with lowland areas, were more susceptible to P papatasi propagation compared to the southern parts, characterized by mountainous and forested areas.…”
Section: Discussionmentioning
confidence: 99%
“… 59 Similarly, another study conducted in Iran in 2018 confirmed the role of wind speed as one of the multiple climatic factors affecting the emergence of CL cases in the study area, using a decision tree model. 53 …”
Section: Discussionmentioning
confidence: 99%